2002
DOI: 10.1139/w02-107
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid induces transcription of laccase genecglcc1in the white-rot fungusCoriolopsis gallica

Abstract: Laccase, a phenoloxidase enzyme secreted by white-rot fungi, has a significant role in the degradation of lignin and environmental pollutants. Coriolopsis gallica is a ligninolytic basidiomycete that produces high levels of this extracellular enzyme. A laccase gene cglcc1 from this fungus has been cloned and sequenced. The capacity of C. gallica to efficiently degrade polyphenols has been successfully applied in our laboratory to the biotreatment and decolorization of several industrial wastewaters. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…It is noteworthy to mention that several fungal species including Aspergillus strains are able to produce laccase (Bajpai & Patil 1996Scherer & Fischer 1998;Kiiskinen et al 2004). On the other hand there are evidences that tannic acid is able to induce laccase activity in some basidiomycetes fungi (Carbajo et al 2002), where a role for oxidative ligninolytic enzymes in the degradation of phenolic fraction of OMWW was proposed (Sayadi & Ellouz 1995;Jaouani et al 2003). Confirmation of the presence of laccase in A. niger HA37 still awaits further investigation.…”
Section: Resultsmentioning
confidence: 94%
“…It is noteworthy to mention that several fungal species including Aspergillus strains are able to produce laccase (Bajpai & Patil 1996Scherer & Fischer 1998;Kiiskinen et al 2004). On the other hand there are evidences that tannic acid is able to induce laccase activity in some basidiomycetes fungi (Carbajo et al 2002), where a role for oxidative ligninolytic enzymes in the degradation of phenolic fraction of OMWW was proposed (Sayadi & Ellouz 1995;Jaouani et al 2003). Confirmation of the presence of laccase in A. niger HA37 still awaits further investigation.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies demonstrated the role of laccases and PPOs in degradation of these compounds, and the activities of these enzymes were found to be enhanced by various inducers (Dekker et al 2001;Maceiras et al 2001;Carbajo et al 2002;DSouza et al 2006). In the present study also caffeic acid, guaiacol, tannic acid and veratryl aldehyde resulted in induced isoform at Rm 0.156 compared with uninduced cells; however, its relative intensity was higher when using veratryl aldehyde (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Our findings revealed that laccase activity enhancement also occurred in tomato juice medium without external inducers, as the activity achieved was higher (11 000 IU/L) than that produced in the optimized glucose-meat peptone medium and CuSO 4 . This medium served as a source of carbon and nitrogen for the growth of P. sanguineus and also might induce the enzyme production on account of its phenolic compounds as flavonoids and tannic acid (Carbajo et al, 2002;Ullrich et al, 2005).…”
Section: Discussionmentioning
confidence: 99%